PENERAPAN PERMAINAN KECIL UNTUK MENINGKATKAN KETERAMPILAN GERAK DASAR BERLARI SISWA SEKOLAH DASAR - Eka Fitri Novita Sari; Kamil Syechabudin; Mochamad Asmawi (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2018)
This study aims to improve basic motor skills running in Class III SDIT AlMarjan Bekasi, West Java. The method used is classroom action research. Alteration or improvement of basic movement skills run the student by applying a small game seen on the results of the assessment process to run the basic motion. The first cycle activities with the following results: 1) students do not understand about the basic motion running. 2) some students still perform basic motion run at will. 3) some students still perform basic motion ran did not mean it. I cycled student mastery value reached (53.33%), there are still very many students who do not get the value specified above KKM school party of 75. The second cycle activities with the following results: 1) the student is able to understand the material of the basic motion ran 2) students are able to perform basic motion running properly and well, 3) students are able to perform basic motion ran earnestly. For completeness initial test student learning outcomes of students otherwise completed a number of 7 students (23.33%), which is otherwisecompleted the first cycle of 16 students (53.33%), and the second cycle students who otherwise completed a total of 30 students (100%).